Multistage Optimization Using a Modified Gaussian Mixture Model in Sperm Motility Tracking - Mohammed Alameri; Khairunnisa Hasikin; Nahrizul Adib Kadri; Nashrul Fazli Mohd Nasir; Prabu Mohandas; Jerline Sheeba Anni; Muhammad Mokhzaini Azizan (Hindawi Publishing, 2024)
Indexed by WOS/SCOPUS/ERA